2020
DOI: 10.33899/ijvs.2019.125613.1104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic acidophilus plus against infection with secondary hydatid disease in BALB /c mice

Abstract: The current study investigated the effect of acidophilus plus probiotic in the immune activities in mice to infestation with the cystic echinococcosis. Two dilutions of the probiotic bacteria 9*10 6 /0.1 ml, 30*10 3 /0.1 ml CFU were used, by intraperitoneally injection in the experimental animals, pre and post infections with protoscoleces of Echinococcus granulosus. Before infection remedy comprised injection by acidophilus plus twice with 72 hours interval, on the seventh day, animals were injected with prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…It may well be concluded that probiotic bacteria can be used as a therapeutic method against hydatidosis. Unfortunately, no immune analysis was done ( Yousif and Ali 2020 ).…”
Section: Probiotics As Complement/treatment Against Helminth Infectionsmentioning
confidence: 99%
“…It may well be concluded that probiotic bacteria can be used as a therapeutic method against hydatidosis. Unfortunately, no immune analysis was done ( Yousif and Ali 2020 ).…”
Section: Probiotics As Complement/treatment Against Helminth Infectionsmentioning
confidence: 99%
“…Diagnosis of cystic echinococcosis is based on imaging techniques, like ultrasound as a major tool for classification of hydatid cysts (6). Whereas serological methods were used for confirmation only (7). Ultrasound is a physical and therapeutic method as non-ionizing radiation in the form of mechanical sound waves to the tissues to raise the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediated host can be infected by orally ingestion of parasite eggs which develop into fluid-filled cysts in their liver, lungs, and other organs [4]. The disease causes expanded mortality and morbidity in human and livestock [5]. Echinococcosis disease is asymptomatic for several years, and the clinical symptoms can appear due to increase of cyst size which cause pressure on nearby tissues [6].…”
Section: Introductionmentioning
confidence: 99%